Layered Metal‐Halide Perovskite Single‐Crystalline Microwire Arrays for Anisotropic Nonlinear Optics. (28th August 2021) - Zhao, Jinjin; Zhao, Yingjie; Guo, Yangwu; Zhan, Xiuqin; Feng, Jiangang; Geng, Yue; Yuan, Meng; Fan, Xin; Gao, Hanfei; Jiang, Lei; Yan, Yongli; Wu, Yuchen
Abstract: Hybrid organic–inorganic metal‐halide perovskites with diverse structure tunability are promising for nonlinear‐optical (NLO) applications, such as frequency conversion and electro‐optic modulation. For integrated NLO devices, single‐crystalline perovskite micro‐ and nanostructures with high quality and multifunctionality are in high demand. However, the fabrication of single‐crystalline perovskites arrays is still challenging in regulating liquid dynamics and crystal growth simultaneously. Herein, a capillary‐bridge‐manipulated strategy is established to steer the dewetting process of microdroplets and provide spatial confinement for crystal growth. These 1D perovskite microwire arrays show regulated geometry, pure orientation, and single crystallinity. Chiral ammonium molecules are introduced into the metal‐halide octahedral quantum wells to break the centrosymmetry of the perovskite, allowing the perovskite to exhibit excellent second‐order NLO properties. The as‐prepared microwire arrays also demonstrate linearly polarized second harmonic generation and two‐photon fluorescence. Microwire arrays exhibit higher second harmonic conversion efficiency compared with their polycrystalline thin‐film counterparts. It is believed that this strategy for the fabrication of chiral perovskite microstructure arrays holds great promise for NLO integrated applications and opens up an avenue to explore multifunctional chiral perovskites. Abstract : Layered chiral perovskite single‐crystalline microwire arrays with pure crystallographic orientation and homogeneous size are fabricated by a capillary‐bridge‐manipulated strategy through controllable fluid dynamics and crystallization. These microwire arrays exhibit excellent nonlinear‐optical properties: strong anisotropy in second harmonic generation (SHG) and two‐photon fluorescence signals; and higher SHG conversion efficiency compared with their polycrystalline thin‐film counterparts.